Products : 50 real-life projects uncovered. - IDSA (Gloucester : Rockport, 2003)
Each project includes complete text describing the designer's insights and inspirations, as well as the evolution of the project illustrated. Working drawings, sketches, process books, computer visuals, storyboards and colour photographs show the story behind the design.
Keywords: Ontwerpen